Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Kinerja Usaha Kecil di kota Makassar - Edy Jumady; Ardiansyah Halim; Dewi Manja; Nurul Qaisah Amaliah (Universitas Negeri Padang, 2022)
This study aims to determine and analyze whether financial literacy and financial inclusion affect the performance of small businesses in Makassar. Collecting data using primary data obtained from questionnaires using a simple random sampling technique. The population is 305 SMEs in the city of Makassar, Mamajang district, while the sample taken is 75 respondents. The results of the questionnaire have been tested for validity and reliability. The classical assumption has also been tested in the form of the normality assumption. The method of data analysis used multiple regression analysis techniques. The results showed that financial literacy had a positive and significant effect on the performance of small businesses in Makassar, while financial inclusion had a negative and insignificant effect on the performance of small businesses in MakassarKeywords: financial literacy, financial inclusion, business performance